1966
DOI: 10.1128/aem.14.6.888-891.1966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Ions on Submicron T1 Bacteriophage Aerosols

Abstract: Effect of air ions on submicron Ti bacteriophage aerosols. Appl. Microbiol. 14:888-891. 1966.-The effect of a high concentration of ionized air molecules on sampling Ti phage aerosols of submicron particle size was evaluated by comparing the phage recoveries of all-glass impingers (AGI-4) and type 6 filter papers. Sampler recoveries of all ionized aerosols were less than the recoveries of nonionized control aerosols. These reductions in recovery were greater with positive ions than with negative ions or ions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Harstad also reported that filters are very destructive for this bacterial virus but are the most efficient at collecting submicrometer particles and that the fritted bubbler is the least efficient sampler, with a physical loss of over 80% of the sample (66). These differences in the recovery rates of AGI samplers and filters were confirmed in a later study (64). The gentler sampling process leading to better recovery of infective viruses seems to be the main reason for the wide use of AGI samplers in aerovirology.…”
Section: Liquid Impactorssupporting
confidence: 52%
See 3 more Smart Citations
“…Harstad also reported that filters are very destructive for this bacterial virus but are the most efficient at collecting submicrometer particles and that the fritted bubbler is the least efficient sampler, with a physical loss of over 80% of the sample (66). These differences in the recovery rates of AGI samplers and filters were confirmed in a later study (64). The gentler sampling process leading to better recovery of infective viruses seems to be the main reason for the wide use of AGI samplers in aerovirology.…”
Section: Liquid Impactorssupporting
confidence: 52%
“…For example, phage X174 is more susceptible to ozone than are phages MS2 and T7 (133). Ions in the air can also reduce the recovery rate of certain viruses, such as aerosolized T1 bacteriophage, with positive ions having the most detrimental effect (64).…”
Section: Factors Affecting the Recovery Of Airborne Viruses By Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The viral aerosol size will depend on a variety of factors, including the aerosol source as well as its nature, its concentration, and its distribution in the environment (Wichmann et al 2000). Several samplers, such as liquid impingers (Verreault et al 2008), slit samplers (Thomas 1970;Dahlgren et al 1961), and filters (Harstad 1965;Happ et al 1966;Tseng and Li 2005) are avail-able to sample viral aerosols. The efficacy of these samplers for airborne viruses most often depends on the recovery of infectious viral particles and, therefore, mainly on the preservation of viral integrity.…”
mentioning
confidence: 99%